Reducing Salt Levels in Sea Water Using Active Carbon Adsorbent from Coconut Shell Charcoal, Silica Sand, and Palm Fiber - Ade Prisma Sitepu; Awy Silaban; Hanifa Azzahra; Raudatul Fadilla; Ummi Kalsum; Moondra Zubir; Lisnwaty Simatupang (Universitas Negeri Medan, 2025)
This study aims to evaluate the effectiveness of various combination of adsorbents in reducing salt content in seawater through the adsorption method. Four variations in the ratio of adsorbent materials, namely activated charcoal, silica sand and palm fiber, were tested with different amounts. activated charcoal, silica sand, and palm fiber, were tested with different amounts. Results showed that the 1:2 ratio (800 grams of activated charcoal and 400 grams of silica sand) resulted in a decrease in salt content from 20% to 3%, which was the highest reduction compared to the other comparison. In addition, the pH test showed that the pH value of the water after the adsorption process remained in the neutral range, namely 7 to 7.5, which indicating that the filtration process successfully improved the water quality. This study indicates that the use of local materials such as activated charcoal and silica sand can be an effective and environmentally friendly solution to reduce the effective and environmentally friendly solution to reduce seawater salinity, as well as increase public awareness of the importance of clean water. public awareness of the importance of clean water. These results are expected to contribute to the development of a more affordable and sustainable desalination technology. technology that is more affordable and sustainable.